2020
DOI: 10.21037/jtd-20-2977
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of circRNA novel_circ_0005280 and its clinical value in the diagnosis of non-small cell lung cancer

Abstract: the mid or advanced stage when they are diagnosed (2,4). Therefore, approaches for preventing and treating NSCLC are needed. It is also important to develop methods for the early diagnosis and accurate prognosis of NSCLC.Circular RNAs (circRNAs) are endogenous non-coding

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…circRNA_102179 promoted the proliferative, migratory, and invasive abilities in NSCLC through the miR-330-5p/HMGB3 axis [ 24 ]. Additionally, several circRNAs also present potential clinical diagnosis value in NSCLC, including circ_0005280, circFARSA, and circRNA_102231 [ 13 , 25 , 26 ]. Our present study have illustrated that hsa_circ_0077837 elevation inhibited cell viability, migration, and invasion in NSCLC and enhanced apoptosis in vitro and inhibited tumorigenesis in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…circRNA_102179 promoted the proliferative, migratory, and invasive abilities in NSCLC through the miR-330-5p/HMGB3 axis [ 24 ]. Additionally, several circRNAs also present potential clinical diagnosis value in NSCLC, including circ_0005280, circFARSA, and circRNA_102231 [ 13 , 25 , 26 ]. Our present study have illustrated that hsa_circ_0077837 elevation inhibited cell viability, migration, and invasion in NSCLC and enhanced apoptosis in vitro and inhibited tumorigenesis in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…For example, it was reported that circRNA_102231 showed increased expression in lung cancer with an area under the ROC curve (AUC) of 0.897, 99 and circ_0005280 was significantly decreased in NSCLC with an AUC of 0.994. 100 Moreover, plasma circ_0001715 levels in lung adenocarcinoma patients were significantly higher than in controls, ROC curve analysis showed that circ_0001715 had a high diagnostic value for lung adenocarcinoma, and the AUC was 0.871. 101 Higher plasma levels of exo-circRNA_0056616 suggested lymph node metastasis of lung adenocarcinoma with an AUC of 0.812.…”
Section: Clinical Prospects Of Circular Rnas In Nsclcmentioning
confidence: 94%
“…The receiver operating characteristic (ROC) curve was used to analyze the sensitivity and specificity of circRNA as a novel tumor biomarker. For example, it was reported that circRNA_102231 showed increased expression in lung cancer with an area under the ROC curve (AUC) of 0.897, 99 and circ_0005280 was significantly decreased in NSCLC with an AUC of 0.994 100 . Moreover, plasma circ_0001715 levels in lung adenocarcinoma patients were significantly higher than in controls, ROC curve analysis showed that circ_0001715 had a high diagnostic value for lung adenocarcinoma, and the AUC was 0.871 101 .…”
Section: Clinical Prospects Of Circular Rnas In Nsclcmentioning
confidence: 99%
“… 183 novel_circ_0005280 down diagnostic and prognostic biomarker low expression of novel_circ_0005280 predicts poor prognosis in NSCLC patients; AUC = 0.944; cutoff 10.23; sensitivity 85.2%; specificity 95.1%; tumor diameter, p = 0.001; and age, p = 0.021 Li et al. 184 hsa_circ_0002130 up diagnostic biomarker hsa_circ_0002130 is highly expressed in serum exosomes from osimertinib-resistant NSCLC patients and shows diagnostic value for NSCLC patients; AUC = 0.792, 95% CI 0.676–0.909 (p < 0.005) Ma et al. 185 hsa_circ_0046264 up diagnostic and prognostic biomarker high expression of hsa_circ_0046264 shows diagnostic and prognostic value for NSCLC patients; AUC = 0.971, sensitivity 95.1%, and specificity 97.3% in the tumor tissues; AUC = 0.915, sensitivity 92.7%, and specificity 95.7% in the serum of the patients; expression of hsa_circ_0046264 is associated with TNM stage (p = 0.015), age (p = 0.03), tumor size (p = 0.017), lymph node metastasis (p = 0.004), and OS (p < 0.05) Liu et al.…”
Section: Clinical Applications Of Circrnas In Nsclcmentioning
confidence: 99%